Waiting for answer This question has not been answered yet. You can hire a professional tutor to get the answer.

# How do you solve using the quadratic formula ##x^2-25=0##?

If you **really must** use the ,
we need to express our equation in the form:
##ax^2+bx+c=0##

##x^2-25=0## becomes ##(1)x^2 +(0)x +(-25) =0##

The quadratic formula tells us the solution(s) is/are ##x=(-b+-sqrt(b^2-4ac))/(2a)## or, for our example ##x=(0 +-sqrt(0^2-4(1)(-25)))/(2(1))##

##x= +-sqrt(100)/2##

##x=+-10/2##

##x=+-5##